2010
DOI: 10.1002/eat.20777
|View full text |Cite
|
Sign up to set email alerts
|

Eeg in adolescent anorexia nervosa: Impact of refeeding and weight gain

Abstract: EEG abnormalities (reduced alpha/increased beta power) in AN normalizes with refeeding, while increased theta power persists in parietal-occipital regions in an eyes closed context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 35 publications
5
27
1
Order By: Relevance
“…Our findings are different for other studies for EEG in anorectic girls which mainly confirmed the dominance of beta brain waves and hyperarousal due to anxiety [28][29][30][31].…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are different for other studies for EEG in anorectic girls which mainly confirmed the dominance of beta brain waves and hyperarousal due to anxiety [28][29][30][31].…”
Section: Discussioncontrasting
confidence: 99%
“…Methodology problems, mainly based on the variability of the samples (age, body mass index, chronicity, medication, experimental tasks, time of EEG testing), could explain the dispute in respect of the relationship between EEG changes/ weight changes 30. Nevertheless, the majority of studies have reported a relationship between weight changes and EEG changes.…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned reduced alpha/increased beta pattern relates to an underweight state in eyes open EEG changes after refeeding (alpha power increases and beta and delta power decreases). Eyes closed underweight patients with anorexia nervosa have elevated theta in parietal-occipital regions, which remains after refeeding 30. The complex reduced alpha/increased beta/increased theta has been related to a high level of cortical activation, which usually appears with high levels of anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hatch et al [49] investigated the resting electroencephalogram (EEG) of 37 adolescent anorexia nervosa patients (mean age 15 years, mean duration of illness 9 months) before and after re-feeding and weight recovery, compared with 45 healthy controls. In the 'eyes-open' condition, there was significantly reduced alpha activity and increased beta frontal activity in the patient group.…”
Section: Prospective Studiesmentioning
confidence: 99%